Dari Salib Ke Perdamaian: Kristologi Kontekstual Sebagai Jembatan Moderasi Beragama Indonesia - Siahaya, Johannis (Shift Key : Jurnal Teologi dan Pelayanan, 2025)
In the context of Indonesian society which is pluralistic and vulnerable to religious-based social friction, a solid theological foundation is needed to build a culture of religious moderation. So far, Christian theology has often been perceived as exclusive because of its focus on the doctrine of salvation, so that it is less considered contributive to interfaith dialogue. However, recent developments in contextual theology and public theology show that Christology—especially through the narrative of the cross and kenosis—has great transformative power in building an inclusive social ethic. This study uses a qualitative-descriptive method with a literature study approach and contextual theological analysis. This study concludes that Christology can be a bridge that spans differences, rejects extremism, and encourages collaboration in building a just, peaceful, and respectful society.